Power and vulnerability: managing sensitive language in organizational communication - Healey, Patrick G. T.; Khare, Prashant; Castro, Ignacio; Tyson, Gareth; Karan, Mladen; Shekhar, Ravi; McQuistin, Stephen; Perkins, Colin; Purver, Matthew (Frontiers in Psychology, 2024)
Organisational responsibilities can bring power but also a degree of exposure to scrutiny. This tension leads to divergent predictions about the use of potentially sensitive language: power might license it, exposure might inhibit it. Data from a large corpus of organisational emails shows that people in positions of relative power are approximately three times less likely to use sensitive words than people more junior to them. This tendency appears to be independent of whether other people are using those words and independently of a whether a particular word occurs in a sensitive context. The results suggest that, in at least some circumstances, the vulnerability associated with greater exposure can be a more significant influence on language use than social power.